2023
DOI: 10.1101/2023.03.25.533209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling individual rhythmic abilities using machine learning

Abstract: Humans can easily extract the rhythm of a complex sound, like music, and move to its regular beat, for example in dance. These abilities are modulated by musical training and vary significantly in untrained individuals. The causes of this variability are multidimensional and typically hard to grasp with single tasks. To date we lack a comprehensive model capturing the rhythmic fingerprints of both musicians and non-musicians. Here we harnessed machine learning to extract a parsimonious model of rhythmic abilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 114 publications
1
5
0
Order By: Relevance
“…Notably, the aforementioned tasks showed excellent test-retest reliability (BAT and paced tapping with music) and are also those found to capture most variability in rhythmic capacities across different BAASTA tests as shown in a recent machine-learning study (Dalla Bella et al, 2023). This finding supports the choice of the two tasks to compute a composite scorethe BTIas a global measure of rhythmic abilities (see also, Puyjarinet et al, 2017 for a first presentation of the BTI).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Notably, the aforementioned tasks showed excellent test-retest reliability (BAT and paced tapping with music) and are also those found to capture most variability in rhythmic capacities across different BAASTA tests as shown in a recent machine-learning study (Dalla Bella et al, 2023). This finding supports the choice of the two tasks to compute a composite scorethe BTIas a global measure of rhythmic abilities (see also, Puyjarinet et al, 2017 for a first presentation of the BTI).…”
Section: Discussionsupporting
confidence: 62%
“…This complexity is difficult to capture through isolated tasks and instead requires multiple assessments, as provided by comprehensive test batteries. Multiple tests afford precise measurement of timing and rhythm abilities, and the detection of individual profiles (Dalla Bella et al, 2023), allowing isolation of the locus of impairment in individuals with rhythm disorders. Existing batteries for testing timing and rhythm abilities include both perceptual and sensorimotor tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated significant individual differences in rhythm perception and rhythm production tasks, both with and without an external stimulus (Dalla Bella et al, 2023;Fiveash et al, 2022;Kragness et al, 2021;Palmer et al, 2014;Rajan et al, 2019;Sowiński & Dalla Bella, 2013;Tierney et al, 2017;Tranchant et al, 2016). Rhythmic abilities fall on a continuum spanning from experts (Dalla Bella et al, 2024), such as professional musicians, to individuals showing poor rhythmic abilities, such as beat deafness or poor synchronization (Bégel et al, 2017;Palmer et al, 2014;Phillips-Silver et al, 2011;Sowiński & Dalla Bella, 2013;Tranchant et al, 2021;Tranchant & Peretz, 2020). At the low end of the continuum, individuals can be impaired specifically in rhythm production (Sowiński & Dalla Bella, 2013), in rhythm perception (Bégel et al, 2017), or both (Palmer et al, 2014;Phillips-Silver et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the low end of the continuum, individuals can be impaired specifically in rhythm production (Sowiński & Dalla Bella, 2013), in rhythm perception (Bégel et al, 2017), or both (Palmer et al, 2014;Phillips-Silver et al, 2011). Thus, measuring both rhythm perception and motor production is paramount to account for individual differences in rhythmic abilities (Dalla Bella et al, 2023, 2024.…”
Section: Introductionmentioning
confidence: 99%